Global and Country-Specific Geopolitical Risks and Exchange Rate Volatility: New Empirical Evidence from Indonesia - Khaliq, Abdul (Jurnal Ekonomi Kuantitatif Terapan; 2022: Vol. 15, No. 2, Agustus 2022 (pp.162-339), 2022)
This paper investigates the conditional predictability of geopolitical risks (GPR) on the rupiah-dollar exchange rate volatility, using 447 monthly observations spanning January 1985 to March 2022. The paper utilizes asymmetric GARCH (1,1) combined with various asymmetric GARCH models, including the integrated GARCH (I-GARCH), the exponential GARCH (E-GARCH), and the threshold GARCH (T-GARCH), and the power asymmetric GARCH (A-PARCH). This study finds convincing evidence that GPRI has a consistent effect on exchange rate volatility, either symmetric GARCH models or asymmetric GARCH models. Interestingly, the global geopolitical risks (GPR) heterogeneously affect the exchange rate volatility of Indonesia. These empirical findings imply that the rupiah-dollar exchange rate volatility is more vulnerable to domestic GPRI than global GPR.